Efficacy of Local Infiltration of Tramadol and Bupivacaine for Postoperative Analgesia in Children Following Herniotomy: Randomized Control Trial - Dahal, Geha Raj; Dokania, Kanishk; Shrestha, Pramesh Sunder; Pokharel, Rameshwar Prasad (Journal of Karnali Academy of Health Sciences, 2020)
Background: Inguinal herniotomy is a common surgical procedure in children. Wound infiltration of local anesthetics during the procedure is a standard technique for post-operative analgesia. Recently, tramadol is shown to be effective analgesic if used locally also. This study was conducted to compare the post-operative pain after local infiltration of bupivacaine and tramadol. Methods: This study was a double blinded randomized controlled trial conducted at pediatric surgery unit of Tribhuvan University Teaching Hospital, Institute of Medicine, Kathmandu, Nepal. A total of 76 children were operated for inguinal hernia during the study period and sixteen children were excluded. Remaining 60 children were randomized into 2 groups: tramadol (T group) and bupivacaine (B group). T group received tramadol and B group received bupivacaine as local wound infiltration at the time of herniotomy. Post - operative pain was evaluated by ‘Modified pain score for children’. Pain score and other variables were compared between the groups. Results: A total of 60 children were randomized into T and B group. Demographic data was comparable. Pain free interval in T group was 7.43 ± 4.41 hours and B group was 6.70 ± 2.46 hours. It was statistical not significant (P=0.42). Pain score at 1, 4, 8, 12 and 24 hours was also similar in the two groups. Conclusion: Local infiltration of Tramadol is as effective as Bupivacaine for postoperative analgesia in children undergoing herniotomy. Tramadol can be used as local infiltration for effective post - operative analgesia.